The Role of Renal Dysfunction in Chronic Heart Failure of Rheumatic Etiology and Therapeutic Possibilities - Sulaymonovna, Khatamova Raykhon (American Journal of Biomedicine and Pharmacy, 2025)
Chronic heart failure (CHF) is one of the most common clinical syndromes among the global population and is considered a severe complication of cardiovascular diseases, as well as one of the leading causes of mortality and disability [23]. CHF has been diagnosed in 1.0–2.6% of the population in Europe, 2.2% in the United States, and 7% in the Russian Federation, with this prevalence increasing with age [12, 15]. Rheumatic heart defects play a significant role in the etiology of CHF, which is associated with their high prevalence, including in Uzbekistan [13, 25]. In CHF, renal dysfunction develops in the form of cardiorenal syndrome, which intensifies the interconnection between the heart and kidneys [25]. In recent years, growing attention has been paid to the cardio- and nephroprotective effects of empagliflozin, a drug from the group of selective sodium-glucose cotransporter 2 (SGLT2) inhibitors [19]. The measures adopted in Uzbekistan to improve healthcare quality and prevent non-communicable diseases further underscore the relevance of this study [PD-60, 2022]. This article examines renal dysfunction and the effects of empagliflozin in CHF that has developed on the background of rheumatic heart defects.